Recurrent labial xanthoma infection in a patient with Neurofibromatosis-Noonan syndrome: case report and literature review - Dussueil Pauline; Sergent Jean-François; Veyssière Alexis; Benateau Hervé (EDP Sciences, 2022)
Introduction: Noonan Syndrome is a clinically and genetically heterogeneous syndrome, characterized by marked phenotypic variability. All the clinical manifestations of this syndrome are still not fully known. Observation: We present the case of a 58-year-old woman with a diagnosis of Neurofibromatosis-Noonan syndrome with SOS2 mutation, observed by her general practitioner for a recurrent left upper lip abscess despite drainage and antibiotic therapy. The anatomo-pathological result of the sample was in favor of an infected xanthoma. Discussion: The most common oral manifestation of Noonan syndrome includes malocclusion, dental anomalies and radiologic jaw lesions. Xanthomas of the lip have never been reported in this syndrome. Conclusion: Oral xanthomas could be one of the many oral clinical manifestations of Noonan Syndrome. However, more research is needed to understand clinical consequences of mutations in identified genes.